ECOLOGICAL AND BIOLOGICAL CHARACTERISTICS AND ASSESSMENT OF THE CURRENT STATE OF THE SPECIES HYLOTELEPHIUM EWERSII (LEDEB.) H. OHBA AND PHEDIMUS HYBRIDUS (L.) 'T HART. IN THE FLORA OF THE KASTEK GORGE OF THE ILE ALATAU (ҚазҰУ хабаршысы. Экология сериясы, 2024)
The article is devoted to the study of the current state of populations of the species Hylotelephium ewersii (Ledeb.) H. Ohba (formerly Sedum ewersii Ledeb.) and Phedimus hybridus (L.) 't Hart (also known as Sedum hybridum L. and Aizopsis hybrida (L.) Grulich) in the floristic composition of the coenopopulations of these species in the Ile Alatau. The article presents a study and analysis of the biology of the populations of H. ewersii and P. hybridus in the Kastek Gorge of the Ile Alatau, the diversity of their life forms, and ecological reactions in specific ecological-cenotic conditions. Seasonal rhythms of development of H. ewersii and P. hybridus showed their stability and high adaptability to the conditions of the landscape mountain zone of the Ile Alatau. The studies made it possible to identify the adaptations of natural cenopopulations of H. ewersii and P. hybridus to long-term, sustainable existence in conditions of a sharply continental climate and to assess their current state. The article presents a taxonomic, ecological, and geographical analysis of the flora of the populations of H. ewersii and P. hybridus. The studied species H. ewersii and P. hybridus have a life form of herbaceous succulent-leafy terrestrial-creeping polycarpics with a rosette-less sympodial model of shoot formation, where, according to the position of the renewal buds, the studied species belong to the chamaephyte biomorphKey words: Hylotelephium ewersii, Phedimus hybridus, population, coenopopulation, Kastek Gorge, Ile Alatau